Analisis Kemampuan Literasi Sosial Siswa Sekolah Dasar pada Pembelajaran IPS - Dahlianti, Revi (Lembaga Anotero Scientific Pekanbaru, 2024)
Social Studies learning in elementary schools plays a strategic role in shaping students’ critical thinking skills, social attitudes, and character. One essential competence that needs to be developed is social literacy, which refers to the ability to understand, analyze, and respond to social issues in the surrounding environment. However, empirical findings indicate that students’ social literacy skills remain limited, particularly in connecting social studies knowledge with real-life contexts. This study aims to analyze the social literacy abilities of elementary school students in Social Studies learning. The research employed a qualitative descriptive method with subjects consisting of fourth and fifth-grade students at an elementary school. Data were collected through observation, interviews, and documentation, and were analyzed using Miles & Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results show that students’ social literacy abilities are at a moderate level, with stronger performance in recognizing simple social problems and demonstrating basic caring attitudes, but weaker in providing critical solutions, ensuring equal participation in discussions, and linking social studies concepts to real-life contexts. The study concludes that strengthening social literacy requires Social Studies learning that is more contextual, collaborative, and experiential, such as project-based approaches or community-based activities. These findings are expected to serve as a foundation for teachers in designing Social Studies learning that emphasizes not only knowledge acquisition but also the development of students’ character and social competence